Enhanced hydrogen photogeneration by bulk g-C3N4 through a simple and efficient oxidation route. Issue 19 (2nd May 2018) - Pisanu, Ambra; Speltini, Andrea; Vigani, Barbara; Ferrari, Franca; Mannini, Matteo; Calisi, Nicola; Cortigiani, Brunetto; Caneschi, Andrea; Quadrelli, Paolo; Profumo, Antonella; Malavasi, Lorenzo
Abstract : The hydrogen production rate under visible light of bulk g-C3 N4 has been improved 8-fold by a simple oxidation process. Abstract : The search for new environment-friendly visible-light absorbing catalysts is an urgent task. g-C3 N4 has excellent photocatalytic properties and the possibility of developing cost-effective routes to make this material a viable alternative to the currently used catalysts is required. In this work, we show that a simple chemical oxidation process of g-C3 N4 with nitric acid allowed significantly enhancing the hydrogen photogeneration from aqueous triethanolamine, under simulated solar light. An 8-fold improvement of the H2 production, with respect to the pristine sample, was achieved by properly controlling the physical–chemical parameters of the oxidation process, reaching a value of about 4000 μmol g −1 h −1, which is one of the highest hydrogen production rates for bulk g-C3 N4 . Such high levels of photocatalytic activity result from the combination of improved surface area and changes in the electronic structure induced by the oxidation process.